Petrogenesis of the volcanic suite of Bouvetøya (Bouvet Island), South Atlantic - Prestvik, Tore; Goldberg, Steven; Goles, Gordon G. (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1999)
Whole rock and mineral compositions of volcanic rocks collected during the Norwegian Polarsirkel expedition (1978/79) to the volcanic istand of Bovetøya (close to the Bouvet Triple Junction) are discussed and compared with previously published data from the island. The rock types, hawaiite, benmoreite, and peralkaline trachyte and rhyolite (comendite) are related to each other by crystal fractionation processes. The trace element and radiogenic isotope signatures displayed by the Bouvetøya rocks are those of a moderately enriched oceanic island suite. On several isotope plots Bouvetøya rocks fall on or close to mixing lines between the euriched EM-l and HIMU mantle components. Mixing between depleted morb mantle (DMM) and euriched components is not likely. Thus, Bouvetøya displays a typical plume signature.
Keywords: Bouvetøya; M/V Polarsirkel; NARE 1978/79; geokjemi; geologi; petrologi

The geology and age of Peter I Øy, Antarctica - Prestvik, Tore; Duncan, Robert A (Polar Research, 1991)
The island Peter I Oy is located in the Bellinghausen Sea 400 km off the coast of West Antarctica. It is situated at the transition between oceanic and contintental crust close to a former transform fault, the Tharp fracture zone. The island is completely volcanic, consisting of predominantly alkali basalt and hawaiite and some more evolved rocks. Sampling done by the Aurora expedition in 1987 has made dating and detailed petrological studies possible. The island appears to be much younger (< 0.5 Ma) than previously believed. However, the volcanic activity responsible for this oceanic island may have lasted for 10-20 Ma. Volcanic activity at the island thus took place at the same time as post-subduction rift-related volcanism took place along the Antarctic Peninsula and in Marie Byrd Land. However, the petrologic data indicate that this may be coincidental and that the Peter I Oy activity is independent and related to transtensional rifting along the Tharp fracture zone.
Keywords: Peter I. Øy; geologi; petrologi

Petrology and geochemistry of Jurassic basalt dykes from Vestfjella, Dronning Maud Land, Antarctica - Furnes, Herald; Neumann, Else-Ragnhild; Sundvoll, Bjørn (Lithos, 1982)
Mineral and whole rocks analyses of 12 Jurassic basalt dykes from Vestfjella, Dronning Maud Land, Antarctica, are presented, and their genesis discussed. On the basis of major oxides and norms the basalts may be classified as olivine and quartz tholeiites. Plotted in the Plag Cpx (Opx + 4Q) and Ol Plag Q projections, the compositions are most compatible with fractional crystallization of olivine, clinopyroxene and plagioclase from a basalt liquid at very low pressure. The ratios between strongly incompatible elements such as Rb, Cs, Zr, Hf, Ta and Th vary considerably, and petrographic mixing calculations give poor fits with respect to Rb, Cs, Ta, Th and light REE. Initial 87Sr/86 Sr ratios range between 0.70347 and 0.70687, and show no correlation with Rb/Sr or any other SIE ratios. The trace element and Sr isotope data thus do not suggest any simple cogenetic petrogenetic model. It is concluded that the basalt melts most plausibly have been contaminated by, or mixed with anatectic melts of crustal material, rather than reflecting mantle heterogeneity.
Keywords: Dronning Maud Land; geokjemi; geologi; petrologi

Stratigraphy and igneous petrology of Southern Heritage Range, Ellsworth Mountains, Antarctica - Hjelle, Audun; Ohta, Yoshihide; Winsnes, Thore S (Results from Norwegian Antarctic Research 1974-1977, 1978)
Sedimentary and magmatic rocks of Late Proterozoic to Late Paleozoic age, from the southern half of Ellsworth Mountains are described. Basic volcanic rocks, mainly agglomeratic, occur abundantly in the lower part of the succession, in the Minaret Group, and in the lower part of the Heritage Group, but are not recorded in the upper part of the Heritage Group. Due to this lithostratigraphic contrast a new classification is proposed: the Heritage Group including the Middle Horseshoe Formation and the Edson Hills Formation. A stratigraphic gap is evident above the Edson Hills Formation and a separate unit--the Dunbar Ridge Formation--is proposed. This formation is of Middle-Upper Cambrian age, with trilobite-bearing limestones. The structure is governed by a major anticline with a NW plunge in the north but almost horizontal in the south. Contrast of fold intensity and fold style below the youngest exposed unit, the Whiteout Conglomerate and a weathered surface above the Crashite Quartzite suggests a late Paleozoic deformation phase. Two phases of magmatism are distinguished. The pre-Middle Cambrian magmatism is dominantly K-alkalic and suggests the beginning of block subsidence at the early stage of a rift tectonics on a continental crust. The presumptive Late Paleozoic magmatism is N-alkalic and tholeiitic, and occurred after the main deformation; however the rocks were regionally metamorphosed in the actinolite-greenschist facies probably in late Paleozoic time. This magmatism is considered to represent an advanced stage of block tectonics. (Auth. mod.)
Keywords: Antarktis; ekspedisjoner; geologi; petrologi; stratigrafi; vulkaner

The geology and petrology of Bouvetøya, south Atlantic Ocean - Imsland, Pall; Larsen, Jørgen Gutzon; Prestvik, Tore; Sigmond, Ellen M (Lithos, 1977)
Keywords: Bouvetøya; forskning; geologi; petrologi

Notes on the geology and petrology of the mountains in Fimbulheimen, Dronning Maud Land - Gjelsvik, Tore (Norsk Polarinstitutt. Årbok 1961, 1962)
On the coastal slope of the great inland ice of Dronning Maud Land, Antarctica, a number of mountain peaks rises above the ice cap. The central part of the nunatak area consists of very coarse grained hornblende-biotite granite, poor in quartz and rich in porphyroblastic microcline crystals. It is cut by foliated or banded gneisses consisting essentially of the same minerals. The granite clearly intersects the gneiss, and both are cut by more fine-grained granite veins as well as by pegmatite. In some places the gneiss contains red garnet crystals, hut with one possible exception it is not proper chamockite.
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; geologi; petrologi

Rocks from the Antarctandes and the Southern Antilles - Barth, Tom. F W; Holmsen, Per; Bruun, Brynjolf (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume II, 1939)
Keywords: Antarktis; Norvegia ekspedisjonen; geologi; petrografi; petrologi

Report on rock-specimens, collected on Roald Amundsen's South Pole Expedition - Schetelig, Jakob (Videnskabs-Selskabets Skrifter : 1, Mathematisk-naturvidenskabelig klasse, 1915)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; petrologi